Effectiveness of Psychological Nursing Intervention Model on improving Sleep Quality of Cancer Patients - Zong, Peili; RN, MAN, Rudena A. Madayag (International Journal of Public Health and Medical Research, 2025)
This study proposes to evaluate the effectiveness of a Psychological Nursing Intervention Model in improving sleep quality among cancer patients. The intervention aims to address poor sleep and its impact on psychological well-being by enhancing coping skills, sleep cognition, and psychological health. Using a pre- and post-intervention design, data will be collected through validated instruments measuring sleep quality and psychological well-being. Statistical analysis will be performed using SPSS 15.0, including paired t-tests to compare pre- and post-intervention scores, ANOVA to assess relationships between sleep quality and psychological factors, and linear correlation analysis. The study aims to provide insights into the potential benefits of psychological nursing interventions in cancer care.